Antacid therapy in idiopathic pulmonary fibrosis: more questions than answers? - Johannson, Kerri A.; Kreuter, Michael (The lancet. Respiratory medicine, 2017)
Summary: Idiopathic pulmonary fibrosis (IPF) is a progressive parenchymal lung disease of complex cause. Gastro-oesophageal reflux (GER) and microaspiration have been proposed as risk factors for the development and progression of IPF, but robust definitive data are few. A recent international guideline conditionally recommended the use of antacid therapy (proton pump inhibitors or histamine-2-receptor antagonists) for patients with IPF, in the absence of oesophageal reflux or symptoms. In this Position Paper, we summarise the literature addressing the association between GER and IPF, and also identify future research priorities that could clarify this issue. We shed light on the process through which the guideline recommendation was achieved and aim to contextualise the recommendation for providers caring for patients with IPF.
Gesehen am 13.10.2018